The gender differences in the displas of self-control problem of women and men - N G Makarova (RUDN Journal of Psychology and Pedagogics, 2009)
Essence descriptions of self-control, exposed from the analysis of looks of domestic and foreign authors on a problem, are presented in the article, the results of the researches showing the gender differences in the displays of self-control and the attempt of explanation of findings is done from the psychological point of view conducted in two cuts are resulted.